2021
DOI: 10.1111/jpn.13654
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on diarrhoea and its mechanism in weaned piglets fed a high‐protein diet

Abstract: In order to pursue faster growth and development of weaned piglets, increased dietary protein (CP) levels were favoured by the pig industry and the feed industry. The digestive organs of piglets were not fully developed at weaning, and the digestive absorption capacity of protein was limited. High‐protein diets can cause allergic reactions in piglets, destroy intestinal structural integrity, reduce immunity, and cause intestinal flora imbalance. Undigested proteins were prone to produce toxic substances, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 109 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…The inconsistency of our results might be related to the test pigs’ breed and the age in the present study, which was different, and the small intestinal microbiota composition was affected differently. A higher CP content in the diet (CP > 20%) affects the intestinal structure and barrier function, thereby affecting intestinal health, which ultimately leads to an increased rate of diarrhea in piglets ( Xia et al, 2022 ). Previously, we found the diarrhea index was increased in the Huanjiang mini-pigs at 5–10 kg BW stage with a higher CP content in the diet (20% CP) compared to the lower CP content (14–16% CP) ( Liu et al, 2022 ), which may be related to the lower Firmicutes abundance and the higher Proteobacteria abundance in the small intestine of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency of our results might be related to the test pigs’ breed and the age in the present study, which was different, and the small intestinal microbiota composition was affected differently. A higher CP content in the diet (CP > 20%) affects the intestinal structure and barrier function, thereby affecting intestinal health, which ultimately leads to an increased rate of diarrhea in piglets ( Xia et al, 2022 ). Previously, we found the diarrhea index was increased in the Huanjiang mini-pigs at 5–10 kg BW stage with a higher CP content in the diet (20% CP) compared to the lower CP content (14–16% CP) ( Liu et al, 2022 ), which may be related to the lower Firmicutes abundance and the higher Proteobacteria abundance in the small intestine of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Protein is one of the most important nutrients for life and a key factor determining whether a diet is healthy or not (Wolfe et al, 2018 ). The selection of dietary protein sources for weaned piglets, especially the application of plant-based proteins, is important in the pig industry because high levels of plant-based proteins in the diet can cause intestinal damage in piglets due to the influence of antigen proteins; this affects the digestion and utilization of protein, the incidence of diarrhea, and the growth performance, resulting in economic losses to animal husbandry (Xia et al, 2022 ). In our experiment, the dietary treatment had no significant effect on the growth performance of weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The increased content of cadaverine from lysine decarboxylation due to SPH treatment observed in this study suggests an increased transformation of lysine towards cadaverine production rather than butyrate production. Moreover, a higher concentration of other amino acid metabolites, including putrescine, ammonia, and isovalerate was also shown after SPH infusion, which may imply that a potential cytotoxity, oxidative stress and inflammation were stimulated in the colon [ 26 ]. Marakova et al reported that both putrescine and cadaverine levels can be used as potential biomarkers for inflammatory bowel disease (IBD) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%